2018
DOI: 10.1097/md.0000000000012943
|View full text |Cite
|
Sign up to set email alerts
|

Tpeak-Tend/QT interval predicts ST-segment resolution and major adverse cardiac events in acute ST-segment elevation myocardial infarction patients undergoing percutaneous coronary intervention

Abstract: Elevated ST-segment and increased Tpeak-Tend interval (Tp-e) were prognostic predictors in major adverse cardiac events (MACEs) in ST-segment elevation myocardial infarction (STEMI). The electrophysiologic relationship between them during percutaneous coronary intervention (PCI) needs to elucidate.Patients with STEMI admitted to hospital were prospectively evaluated. ST-segment resolution (STR) (defined as ≥50% reduction as the complete-STR [CSTR] group, <50% as incomplete-STR [ISTR] group), Tp-e interval, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
2
10
2
2
Order By: Relevance
“…12,13 An increase or prolongation in the Tp-e interval or Tp-e/QT ratio is considered an index of arrhythmogenesis in all cases of long, normal, or short QT intervals, or in acquired or congenital channelopathies. 14 Although Uçar et al found the Tp -e interval or Tp-e/QT ratio to be significantly higher in the group of acute myocarditis patients compared to the control group, it should be noted that the control group in their study is consisted of completely healthy volunteers. The normal value of the Tp-e/QT ratio is around 0.192 ± 0.35.…”
Section: Discussionmentioning
confidence: 79%
“…12,13 An increase or prolongation in the Tp-e interval or Tp-e/QT ratio is considered an index of arrhythmogenesis in all cases of long, normal, or short QT intervals, or in acquired or congenital channelopathies. 14 Although Uçar et al found the Tp -e interval or Tp-e/QT ratio to be significantly higher in the group of acute myocarditis patients compared to the control group, it should be noted that the control group in their study is consisted of completely healthy volunteers. The normal value of the Tp-e/QT ratio is around 0.192 ± 0.35.…”
Section: Discussionmentioning
confidence: 79%
“…Because variant angina has the characteristic ischemia that can be completely reversed, it can be used as a model to study the relationship between STE and MVAEs. Moreover, our study showed that in patients with STEMI undergoing primary percutaneous coronary intervention (PCI), the duration of ST-segment resolution (STR) can predict malignant arrhythmia and long-term prognosis, and STE is related to the electrophysiological mechanism of the prolonged Tp-e interval [8]. Other studies have suggested that a prolonged Tp-e interval and elevated ST segment amplitude are independent risk factors for reperfusion VF in unselected patients with STEMI [9,10].…”
Section: Introductionmentioning
confidence: 68%
“…The presence of STR after both pharmacological and mechanical reperfusion therapy is highly predictive of infarct-related artery patency and the degree of effective microvasculature perfusion, which was inversely related to infarct size. Thus, STR was shown to be a significant independent predictor of major adverse cardiovascular events and target vessel revascularization in short-and long-term follow-ups [8,24]. STE represented the size of the acute infarcted myocardial area and the resulting potential gradient in the infarcted and non-infarcted regions leading to malignant arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…При анализе полученных результатов определено эффективное влияние эплеренона у пациентов, перенесших ОКСпST с ФВ ЛЖ =40-49%, после проведеной реперфузии миокарда на предикторы ВСС [5]. У пациентов с ХСНпST необходимо оценивать показатели дисперсий интервала QT и его отрезков и их корригированные по ЧСС значения [4].…”
Section: Discussionunclassified
“…Необходимо отметить, что использование как самого интервала QT и его дисперсии, так и его частей, имеет независимый от других сопутствующих факторов характер изменений при прогнозировании желудочковых та-хиаритмий при ОКСпST. Также доказана прогностическая значимость увеличения дисперсии интервала QT при ОКСпST и снижение ее после проведения ЧКВ [5,6].…”
Section: Introductionunclassified